2004
DOI: 10.17221/5711-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of Escherichia coli O157 strains isolated from humans, cattle and pigs

Abstract: A total of 90 Escherichia coli O157 isolates recovered from humans, cattle, and pigs, were examined for the presence of the H7 antigen, ability to produce Shiga toxins and enterohemolysin as well as for antimicrobial resistance and biochemical properties. Fourteen of the human strains (n = 23) and 21 of the bovine isolates (n = 29) were of the O157:H7 serotype as determined by agglutination and PCR methods. All E. coli O157 of porcine origin (n = 38) were H-negative. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
2
6
0
2
Order By: Relevance
“…Similar results for predominance of stx2 producing strains were reported by Wani et al, (2003); Blanco et al, (2004);Osek (2004); Hazarika et al, (2007);Milnes et al, (2008);and Salnec et al, (2009). In this study lower prevelance of stx1 is reported which is similar to finding reported by Galland et al, (2001); Blanco et al, (2004);Osek (2004); Arya et al, (2008) and Milnes et al, (2008).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results for predominance of stx2 producing strains were reported by Wani et al, (2003); Blanco et al, (2004);Osek (2004); Hazarika et al, (2007);Milnes et al, (2008);and Salnec et al, (2009). In this study lower prevelance of stx1 is reported which is similar to finding reported by Galland et al, (2001); Blanco et al, (2004);Osek (2004); Arya et al, (2008) and Milnes et al, (2008).…”
Section: Resultssupporting
confidence: 91%
“…However, lesser isolation rate for stx positive E. coli isolates has been reported by Rahman (2002) and Chattopadhyay et al, (2003). Detailed result is given in Galland et al, (2001); Wani et al, (2003) and Osek (2004) which is in contrast to lower prevalence as reported by Blanco et al, (2004); Mora et al, (2007) and Arya et al, (2008).…”
Section: Resultsmentioning
confidence: 51%
“…In PCR analysis of their results, 26.0% (25/96) of the non‐sorbitol positive E. coli O157:H7 + and all of the E. coli O157:H7 ‐ isolates harbored one or more antibiotic resistance genes, while tetA, tetB, tetC, strA, strB and sulI genes were detected from a number of the isolates, tetD, tetE, tetG, cmlA, floR, sulII, aadA and ampC genes were not detected in any of the isolates. Osek () reported similar results. He showed that phenotypic characterization of antibiotic resistance in E. coli strains can further approved by the genotypic identification.…”
Section: Discussionsupporting
confidence: 57%
“…It was continued by 35 cycles, each cycle including denaturation 60 seconds at 94°C, annealing 30 seconds at 53°C, and extension 60 seconds at 72°C. Final extention was done 7 minutes at 72°C (Osek, 2004;Pradel et al 2000). from puppies and adult dogs with diarrhea at a percentage (68.75%) and from puppies and adults without diarrhea at a percentage (7.95%).…”
Section: C-thermo-cycler Programmentioning
confidence: 99%